MENCARI FORMAT MODEL ORGANISASI YANG TEPAT UNTUK PESANTREN (IAIN Kediri, 2015)
Pesantren is the oldest Islamic education in Indonesia and attracts a large number of researches. Given that it hasÂ developed and transformed itself into various types, generalization is almost impossible to be made. PesantrenÂ is a unique educational institution and organization. This article attempts to examine the organizational modelÂ of the pesantren with a focus on its dictintive character. It argued that pesantren is based on a holistic modeÂ of organizational system, which is â€˜barÄkahâ€™. The â€˜barÄkahâ€™ or â€˜ngalap barÄkahâ€™ is an open system that is whatÂ distinguishes pesantren from other educational institutions in general. This article also addresses the questionÂ on what kind of organizational format that may be best implemented in pesantren.Keywords: Pesantren, BarÄkah, Organisasi